Expendable Launch Systems - Chilton, Kira, author 648276 (Delhi, India : Library Press : World Technologies, 2012)
Ariane is a series of a European civilian expendable launch vehicles for space launch use. The name comes from the French spelling of the mythological character Ariadne; the word is also used in French to describe some types of hummingbird. France first proposed the Ariane project and it was officially agreed upon at the end of 1973 after delicate discussions between France, Germany and the UK. The project was Western Europe's second attempt to develop its own launcher following the unsuccessful Europa project. The Ariane project was code-named L3S (the French abbreviation for third-generation substitution launcher). The European Space Agency (ESA) changed the EADS subsidiary EADS Astrium to the development of all Ariane launchers and of the testing facilities, while Arianespace, a 32.5% CNES commercial subsidiary created in 1980, handles production, operations and marketing. Arianespace launches Ariane rockets from the Center Spatial Guyanais at Kourou in French Guiana , where the proximity to the equator gives a significant advantage for the launch. The several versions of the launcher include : Ariane 1, first successful launch on December 24, 1979 30, 1986 failed) Ariane 2, first successful launch on November 20, 1987 (the first launch on May) Ariane 3, first successful launch on August 4, 1984, Ariane 4, first successful launch on June 15, 1988, Ariane 5, first successful launch on October 30, 1997 (the first launch on June 4, 1996 failed)